The mitochondria-targeting peptide elamipretide diminishes circulating HtrA2 in ST-segment elevation myocardial infarction. Issue 8 (December 2019) - Hortmann, Marcus; Robinson, Samuel; Mohr, Moritz; Mauler, Maximillian; Stallmann, Daniela; Reinöhl, Jochen; Duerschmied, Daniel; Peter, Karlheinz; Carr, James; Gibson, C Michael; Bode, Christoph; Ahrens, Ingo
Background: The extent of myocardial damage in patients with ST-segment elevation myocardial infarction (STEMI) depends on both the time to reperfusion as well as injury induced by ischaemia–reperfusion resulting in a cascade of cellular and humoral reactions. As a consequence of ischaemia–reperfusion in the heart, the high-temperature requirement serine peptidase 2 (HtrA2) is translocated from the mitochondria to the cytosol, whereupon it induces protease activity-dependent apoptosis mediated via caspases. Myocardial damage induced by reperfusion cannot be monitored due to a current lack in specific biomarkers. We examined the serum level of HtrA2 as a potentially novel biomarker for mitochondrial-induced cardiomyocyte apoptosis. Methods: After informed consent, peripheral blood was obtained from patients ( n =19) with first-time acute anterior STEMI after percutaneous coronary intervention. Within this group, 10 of the patients received the mitochondria-targeting peptide elamipretide (phase 2a clinical study EMBRACE (NCT01572909)). Blood was also obtained from a control group of healthy donors ( n =16). The serum level of HtrA2 was measured by an enzyme-linked immunosorbent assay (ELISA). In a murine model of myocardial ischaemia–reperfusion injury, HtrA2 was determined in plasma by ELISA after left anterior descending artery occlusion. Results: HtrA2 median was significantly increased in patients with STEMI compared to healthy controls 392.4 (240.7–502.8) pg/mL vs. 1805.5 (981.3–2220.1) pg/mL ( P ⩽0.05). Elamipretide significantly reduced the HtrA2 median serum level after myocardial infarction 1805.5 (981.3–2220.1) pg/mL vs. 496.5 (379.4–703.8) pg/mL ( P ⩽0.05). Left anterior descending artery occlusion in mice significantly increased HtrA2 mean in plasma (117.4 fg/ml±SEM 28.1 vs. 525.2 fg/ml±SEM 96; P ⩽0.05). Conclusion: Compared to healthy controls, we found significantly increased serum levels of HtrA2 in patients with STEMI. The result was validated in a murine model of myocardial ischaemia–reperfusion injury. In humans the increased serum level was significantly reduced by the mitochondria-targeting peptide elamipretide. In conclusion, HtrA2 is detectable in serum of patients with STEMI and might present a novel biomarker for mitochondrial-induced cardiomyocyte apoptosis. Consequently, HtrA2 may also show promise as a biomarker for the identification of ischaemia–reperfusion injury. However, this must be validated in a lager clinical trial.